Accidental Cutaneous Burns Secondary to Salbutamol Metered Dose Inhaler - Ashutosh Kale; Fiona Shackley (Case Reports in Medicine)
We report a case of accidental cutaneous burns caused by salbutamol metered dose inhaler. A 9-year-old boy underwent dental extraction at a children's hospital and was incidentally noted to have burn injuries on dorsum of both hands. On questioning, the boy revealed that a few days ago his 14-year-old brother, who is an asthmatic, playfully sprayed his salbutamol metered dose inhaler on the back of both his hands with the inhaler's mouth piece being in direct contact with the patient's skin. On examination, there was a rectangular area of erythema with superficial peeling on the dorsum of both hands, the dimensions of which exactly matched those of the inhaler's mouthpiece. It is possible that the injury could have been a chemical burn from the pharmaceutical/preservative/propellant aerosol or due to the physical effect of severe cooling of the skin or mechanical abrasive effect of the aerosol blasts or a combination of some or all the above mechanisms. This case highlights the importance of informing children and parents of the potentially hazardous consequences of misusing a metered dose inhaler.